Forms of global governence - M. V. Kharkevich (Vestnik MGIMO-Universiteta)
Global governance as a concept defines the meaning of contemporary world politics both as a discipline and as reality. Interdependent and globalized world requires governance, and a global government has not been formed yet. The theoretical possibility of global governance without global government is proved and justified. The purpose of this article is to analytically identify possible forms of global governance. Three such forms of global governance are identified: hierarchical, market and network. In a hierarchy the governance is due to the asymmetry of power between the parties. Market control happens via anonymous pricing mechanism. Network, in contrast to the market is characterized by a closer value link between the actors, but unlike the hierarchical relationship actors are free to leave the network. Global governance takes three forms and is being implemented by different actors. To determine the most efficient form of global governance is impossible. Efficiency depends on the match between a form and an object of government. It should be noted that meta governance is likely to remain a monopoly of institutionally strong states in global governance.